Understanding of HIV and AIDS-Related Messages Among the Key Populations (Voice: A Biannual & Bilingual Journal, 2025)
For effective communication, it is important to find out how the target populations interpret and understand the messages. A descriptive phenomenological study was carried out in Banke district of Nepal to explore the understanding of HIV and AIDS-related messages among the key populations. In-depth interviews were carried out with nine participants selected through purposive and snowball sampling from sexual minority people, and female sex workers. Four emergent themes and eight clusters of themes were identified during data analysis. The participants had a better understanding of safer sex, and the use of PrEP and ARV. On the other hand, some words, symbols, and pictures presented in the messages were still confusing to the participants. This study suggests that clear, precise, explanatory, and illustrative messages in the local language of the target population would be more comprehensible.